1992
DOI: 10.1172/jci116124
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity of protein and glucose metabolism in human forearm skeletal muscle.

Abstract: IntroductionPhysiologic increases of insulin promote net amino acid uptake and protein anabolism in forearm skeletal muscle by restraining protein degradation. The sensitivity of this process to insulin is not known. Using the forearm perfusion method, we infused insulin locally in the brachial artery at rates of 0.00 (saline control), 0.01, 0.02, 0.035, or 0.05 mU/min per kg for 150 min to increase local forearm plasma insulin concentration by 0, -20, -35, -60, and -120 ,U/ml (n = 35). L-Iring-2,6-3Hjphenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
5
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 34 publications
13
109
5
2
Order By: Relevance
“…The changes induced by the administration of rhGH were reversed by rhGH discontinuation. Baseline rates of appearance and disposal of phenylalanine measured in this group of malnourished patients are about 30% lower than those measured in well nourished CRF patients under unrestricted diets (4,29) and are also in the lower range of the values recorded in normal subjects in the literature (23,30) and in our laboratory (4). This observation suggests that low rates of protein synthesis occur in the muscle of malnourished HD patients and is in accordance with studies showing a decrease in RNA/DNA ratio in muscle in such patients (31).…”
Section: Discussionmentioning
confidence: 55%
“…The changes induced by the administration of rhGH were reversed by rhGH discontinuation. Baseline rates of appearance and disposal of phenylalanine measured in this group of malnourished patients are about 30% lower than those measured in well nourished CRF patients under unrestricted diets (4,29) and are also in the lower range of the values recorded in normal subjects in the literature (23,30) and in our laboratory (4). This observation suggests that low rates of protein synthesis occur in the muscle of malnourished HD patients and is in accordance with studies showing a decrease in RNA/DNA ratio in muscle in such patients (31).…”
Section: Discussionmentioning
confidence: 55%
“…Meta-analysis of study characteristics A total of 13 articles [16,[19][20][21][24][25][26][27][28][29][30][31][32], containing 25 experimental studies using different insulin concentrations, were identified for inclusion in the meta-analysis (Table 1); all analysed the effect of insulin on both MPS and MPB (Table 1). A total of 173 individuals were included in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The role of insulin in adult human skeletal muscle is more complex and subject to interplay between other factors such as AA availability, muscle blood flow and microvascular recruitment [16,17]. This has led to various studies reporting opposing conclusions when it comes to the relationship between insulin and human skeletal muscle protein turnover [16][17][18][19][20][21][22]. We therefore undertook a systematic review and meta-analysis in an attempt to clarify the role of insulin in regulating muscle metabolism in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular signaling mechanisms that activate both apoptotic and the Ub-P'some pathways to cause loss of muscle protein remain obscure. One potential mechanism involves insulin/IGF-1 signaling pathways because the predominant effect of insulin on protein turnover in humans is to reduce protein degradation (8). Moreover, insulin resistance is common to metabolic acidosis, uremia, and other catabolic conditions that are associated with activation of the Ub-P'some system (9 -11).…”
mentioning
confidence: 99%